2008
DOI: 10.1111/j.1467-7687.2008.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical neural functions underlying phonological processing and silent rehearsal in children who stutter

Abstract: Phonological processing was examined in school-age children who stutter (CWS) by assessing their performance and recording event-related brain potentials (ERPs) in a visual rhyming task. CWS had lower accuracy on rhyming judgments, but the cognitive processes that mediate the comparisons of the phonological representations of words, as indexed by the rhyming effect (RE) ERP, were similar for the stuttering and normally fluent groups. Thus the lower behavioral accuracy of rhyming judgments by the CWS could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 55 publications
3
71
1
Order By: Relevance
“…For example, AWS have also shown slower RTs on tasks requiring monitoring of phonological structure (such as judging whether stimuli rhyme) and lexical analysis (making semantic category judgments; Bosshardt, 1993Bosshardt, , 1994Weber-Fox, Spruill, Spencer, & Smith, 2008), as well as while monitoring for particular phonemes (Sasisekaran, De Nil, Smyth, & Johnson, 2006). Some of these effects are exacerbated under conditions of increased cognitive load (Weber-Fox et al, 2004) Weber-Fox and colleagues noted that the data to date are "consistent with the hypothesis that underlying neural processes mediating lexical access may operate atypically in adults who stutter in the absence of overt speech" (Weber-Fox et al, 2004, p. 1246.…”
Section: Lexical Processing In People Who Stuttermentioning
confidence: 98%
“…For example, AWS have also shown slower RTs on tasks requiring monitoring of phonological structure (such as judging whether stimuli rhyme) and lexical analysis (making semantic category judgments; Bosshardt, 1993Bosshardt, , 1994Weber-Fox, Spruill, Spencer, & Smith, 2008), as well as while monitoring for particular phonemes (Sasisekaran, De Nil, Smyth, & Johnson, 2006). Some of these effects are exacerbated under conditions of increased cognitive load (Weber-Fox et al, 2004) Weber-Fox and colleagues noted that the data to date are "consistent with the hypothesis that underlying neural processes mediating lexical access may operate atypically in adults who stutter in the absence of overt speech" (Weber-Fox et al, 2004, p. 1246.…”
Section: Lexical Processing In People Who Stuttermentioning
confidence: 98%
“…ERPs are sensitive indicators of language proficiency in children and adults even when the range of participants' proficiencies is within normal limits Pakulak & Neville, 2010). In a series of studies from our laboratory, we have used paradigms that elicit well-known languagerelated ERP components (e.g., N400, P600) to determine if and how neural activity patterns mediating semantic, syntactic, and phonological processing differ for AWS and CWS compared with their fluent peers (e.g., Cuadrado & WeberFox, 2003;Mohan & Weber, 2015;Usler & Weber-Fox, 2015;Weber-Fox, 2001;Weber-Fox & Hampton, 2008;Weber-Fox, Hampton Wray, & Arnold, 2013;Weber-Fox, Spencer, Spruill, & Smith, 2004;Weber-Fox, Spruill, Spencer, & Smith, 2008). The N400 component reflects the identification, retrieval, and integration of semantic meaning (Kutas & Federmeier, 2011), and the P600 is thought to index reanalysis and repair processes, often for violations of syntax or grammar or garden path sentences (Gouvea et al, 2010).…”
Section: Language Aspects Of Stutteringmentioning
confidence: 99%
“…To the best of our knowledge, only a few studies have examined the neural correlates of stuttering in children (Beal et al, 2011;Beal, 2010;Chang et al, 2008;Kaganovich et al, 2010;Sato et al, 2011;Weber-Fox, Spruill, Spencer, & Smith, 2008;Weber-Fox, Hampton Wray, & Arnold, 2013). Neuroanatomical studies conducted by Chang et al (2008) and Beal (2010) showed reduced gray matter volume in children who stutter (CWS) in the left inferior frontal gyrus, and in temporal regions, compared to typically developing children with fluent speech.…”
mentioning
confidence: 99%